THE INTEGRATION OF RELIGIOUS MODERATION IN ENGLISH AS A FOREIGN LANGUAGE (EFL) SETTING: STUDENTS’ AND TEACHERS’ VOICES - Rohmana, Wahyu Indah Mala; Kamal, Shofia; Amalia, Afdhirotul Isna; Ating, Jenab Paruk (Abjadia : International Journal of Education, 2024)
This case study research explores the integration of religious moderation within setting of EFL (English as a Foreign Language) classrooms, specifically in an Islamic Junior High School. The primary objective of this study is to investigate the religious moderation integration into the educational process and to capture the perspectives of both teachers and students. The study employed qualitative approach particularly case study research design which was conducted within one of Islamic junior high school in East Java. Ten students and four English teachers were selected using purposive sampling to participate in the study. Data was collected through interviews, documentation, and observation. The results indicate that religious moderation has been effectively integrated into the teaching and learning process, including lesson planning and thematic material, by the teachers. Tolerance, anti-violence, accommodating to tradition/culture, cultural sensitivity, and open mindedness were the aspect of religious moderation found in EFL classroom.The perception of the teachers on the integration of religious moderation in EFL classrooms are linked to their roles as educators, the act of students, and the diverse backgrounds of the students. Students have reported that the integration of religious moderation has allowed them to gain insights into both appropriate and inappropriate aspects of another culture as they learnt English.